Evangeline in Louisiana: The Acadian-Cajun Connection - Ross, Rita (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1991)
For the French-speaking Acadians of the Canadian Maritimes and the Cajuns of Louisiana, the heroine of Longfellow’s long narrative poem Evangeline (1847) lives on. An important symbol of ethnie history and survival, she represents as well the ties between Acadians and Cajuns. She has become a legendary figure — in Louisiana she even has a different name. This paper explores similarities and différences between the two traditions and the rôle of Evangeline in the Acadian-Cajun connection.